Rare localized high grade chondrosarcoma - Guitton Arteaga, Walter (2021)
Chondrosarcoma is a skeletal malignant neoplasm characterized by the production of neoplastic cartilage, it represents only 20% of bone tumors, and its most frequent location is in the pelvis and proximal extremities. Location in small bones is very rare. A 44-year-old man with a 1-year illness who attended the trauma emergency at the hospital with an increase in volume of the back of the right foot accompanied by intense pain. A wide margin resection of the tumor was performed. The pathology department reported high-grade chondrosarcoma. Currently the patient is evaluated by the oncology service.